Relationship Between Osteopontin Biochemical Parameters and BMD Status in Iraqi Postmenopausal Women with Osteoporosis - Shamsulddin, Hadeer H.; Salih, Lina A.; Eleiwe, Samia A. (Iraqi Journal of Science, 2020)
Osteopontin hormone (OPN) is an extracellular matrix protein that is expressed in bone cells such as osteoblasts and osteoclasts and associated with bone turnover and bone mineral density (BMD) in postmenopausal women with osteoporosis. The aim of the study is to investigate serum levels of circulating OPN and its relationship with biochemical parameters and BMD in postmenopausal women with osteoporosis in Iraq. Serum samples from fifty postmenopausal women were selected from patients attending two educational hospitals in Baghdad, which are AL Wasity Educational Hospital and Baghdad Educational Hospital, during the period from November 2018 to March 2019. Twenty five postmenopausal healthy women were included as a control group. The studied subjects’ ages were in the range of 45-65 years. Dual energy X-ray absorptiometry (DEXA) was the device used to measure bone mineral density and diagnose osteoporosis in both groups. Blood samples were collected from each participant for measuring the serum levels of biochemical parameters (P, Alp, Ca, and OPN) The results of the demographic parameters showed a significant (P≤0.05) increase in mean values of age, menopause duration, and duration of productive life in the patients as compared to the control group. Also, strong positive correlations between patients and the control were recorded in age and duration of productive age, with a weak inverse correlation in menopause duration. While a significant (P≤0.05) decrease in the mean value of body mass index (BMI), BMD, and T-score as compared to the control. The correlation in BMI was weak significant positive while in the other two parameters it was weak significant inverse. The results of the present study showed non-significant differences (P ≥0.05) between the patients and control group for serum biochemical parameters.It was also noticed that there was a significant (P≤0.05) increase in the mean value of osteopontin hormone level in the patients as compared to the control, with a weak significant inverse (p≤0.05) correlation.